Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3173647
|View full text |Cite
|
Sign up to set email alerts
|

Group vs Individual

Abstract: Figure 1. Our cross-device Overview + Detail environment: (a) a tabletop interface containing an overview map of the analysis area, data icons depicting locations with associated geotagged data, and Region of Interest (ROIs) for each collaborator, and (b) a tablet interface that displayed a "detail" view for associated geotagged data within the bounds of the user's ROI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…As our tasks do not require domain-specific knowledge, we did not test them with real highly-trained crisis management operators. A similar approach has also been taken by previous work motivated by real-world contexts [31,32,45].…”
Section: Study Design Participants and Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…As our tasks do not require domain-specific knowledge, we did not test them with real highly-trained crisis management operators. A similar approach has also been taken by previous work motivated by real-world contexts [31,32,45].…”
Section: Study Design Participants and Apparatusmentioning
confidence: 99%
“…When the shared display is horizontal, studies showed that the bigger the shared display, the harder it is to maintain good workspace awareness [65], and that up-close interaction improve workspace awareness; however, distant interaction provides better support for parallel work [31]. When the shared display is vertical, studies showed [59] that if it replicates the shared workspace it is better for grounding close collaboration; but that if it shows only status information, it is better for overall monitoring.…”
Section: Related Workmentioning
confidence: 99%
“…Usually, these setups distribute an interface across a number of devices like tablets, smartphones, interactive walls or tabletops, and provide techniques to effectively use the input/output modalities of these multi-device setups. The research has led to the exploration of supporting both individual tasks [7,20] and collaborative activities [9,11,38,46].…”
Section: Cross-device Systems and Trackingmentioning
confidence: 99%
“…Topics investigated by researchers include table size, Human-Computer Interfacing, device orientation, etc. (Buisine, Besacier, Aoussat, & Vernier, 2012;Homaeian, Goyal, Wallace, & Scott, 2018;Mercier, Higgins, & Joyce-Gibbons, 2014;Ryall, Forlines, Shen, & Ringel Morris, 2004;Zagermann et al, 2016) Some researchers have also begun integrating vertical surfaces. For example, Rogers and Lindley (2004) conducted experiments to examine how the physical orientation of different work surfaces impact collaboration.…”
Section: Tactile and Tabletop Technologies: Physical-digital Workpacesmentioning
confidence: 99%